(An occasional paper) (London, 1978)
In this text, some of the leading authorities in the field bring together current research and sound practical advice on the provision of quality teaching and learning for overseas students. The text represents a wide range of overseas students' experiences from the Pacific Rim, China and the European Community.
Keywords: English language,Language and languages; Study and teaching,Study and teaching